Preclinical Evaluation of a Ratio-Optimized BALIMONT Multi-Strain Synbiotic Platform for Intestinal Flora Regulation - Ziraoui, Anas; Noah Parker, William Fairfax · (International Journal of Public Health and Medical Research, 2026)
We evaluated a BALIMONT multi-strain synbiotic platform built around Bifidobacterium longum, Bifidobacterium adolescentis, and Lactiplantibacillus plantarum, with fructooligosaccharide and stachyose as prebiotic supports. We reorganized the formulation dossier into a journal-style manuscript and interpreted the disclosed mouse outcomes alongside current probiotic and synbiotic literature. Across the disclosed high-dose groups, all six ratio-optimization embodiments increased bifidobacteria and lactobacilli while reducing Escherichia coli; total short-chain fatty acids and butyrate rose in parallel with lower cecal pH, higher fecal-pellet output, and greater fecal moisture. Within the B. longum-enriched branch, the 3:1:1 ratio produced the strongest reported metabolic profile, including total SCFA 93.27 μmol/g and butyrate 19.51 μmol/g. Within the B. adolescentis-enriched branch, the 1:3:1 ratio reached total SCFA 89.48 μmol/g, butyrate 18.81 μmol/g, bifidobacteria 11.38 lgCFU/g, and cecal pH 5.52. Published evidence indicates that FOS increases colonic bifidobacteria in humans, raffinose-family oligosaccharides can be utilized by bifidobacteria and lactobacilli, and synbiotics can raise Lactobacillus and propionate in healthy adults [4-8]. Taken together, these results support BALIMONT as a strain-defined, freeze-dried, prebiotic-supported synbiotic platform whose strongest disclosed effects were observed when bifidobacterial weighting was increased.